Histologic Characteristics and KIT Staining Patterns of Equine Cutaneous Mast Cell Tumors. (May 2014) - Clarke, L.; Simon, A.; Ehrhart, E. J.; Mulick, J.; Charles, B.; Powers, B.; Duncan, C.
Mast cell tumors are uncommon in horses and typically have a benign clinical course, but there are occasional reports of more aggressive behavior. The objective of this study was to review histologic features and KIT expression patterns of 72 previously diagnosed equine cutaneous mast cell tumors to determine if either is associated with clinical outcomes. Biopsy specimens were reviewed using histologic criteria derived from grading schemes, and KIT antibody expression patterns used in canine tumors and surveys were sent to referring veterinarians for follow-up clinical data. Arabians were overrepresented relative to the reference population. Most tumors were well differentiated with low mitotic rates (96%), and aberrant KIT staining patterns, as described in dogs, were uncommonly identified (12%). Associated clinical disease was uncommon and no tumors exhibited malignant behavior. Overall, KIT staining pattern and histologic features were not associated with poor clinical outcome or abnormal tumor behavior.